Efficacy and safety of a music-therapy facilitated pulmonary telerehabilitation program in COPD patients: the COPDMELODY study protocol - Shi, Minghui; Yang, Lulu; Qumu, Shiwei; Lei, Jieping; Huang, Ke; He, Ruoxi; Niu, Hongtao; Dong, Fen; Wang, Siyuan; He, Jiaze; Yang, Ting (Frontiers in Medicine, 2024)
Despite considerable evidence for the benefit in chronic obstructive pulmonary disease (COPD), the implementation of pulmonary rehabilitation (PR) is insufficient. However, music therapy may help address this gap due to its unique benefits. Therefore, we aimed to develop a music-therapy facilitated pulmonary telerehabilitation program based on rhythm-guided walking, singing, and objective telemonitoring. A supervised, parallel-group, single-blinded, randomized controlled clinical trial will be conducted, including 75 patients with COPD anticipated to be randomized in a 1:1:1 ratio into three groups. The intervention groups will receive a 12-week remotely monitored rehabilitation program, while the usual care group will not receive any rehabilitation interventions. Of the two intervention groups, the multi-module music therapy group will contain rhythm-guided walking and singing training, while the rhythm-guided walking group will only include music tempoguided walking. The primary outcome is the distance of the incremental shuttle walking test. Secondary outcomes include respiratory muscle function, spirometry, lower extremity function, symptoms, quality of life, anxiety and depression levels, physical activity level, training adherence, and safety measurements. The results of this study can contribute to develop and evaluate a homebased music-facilitated rehabilitation program, which has the potential to act as a supplement and/or substitute (according to the needs) for traditional center-based PR in patients with stable COPD.